2018
DOI: 10.5194/amt-2018-380
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The SPARC water vapour assessment II: Profile-to-profile comparisons of stratospheric and lower mesospheric water vapour data sets obtained from satellites

Abstract: Abstract. Within the framework of the second SPARC (Stratosphere-troposphere Processes And their Role in Climate) water vapour assessment (WAVAS-II), profile-to-profile comparisons of stratospheric and lower mesospheric water vapour were performed considering 33 data sets derived from satellite observations of 15 different instruments. These comparisons aimed to provide a picture of the typical biases and drifts in the observational database and to identify data set specific problems. The observational databas… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 29 publications
3
4
0
Order By: Relevance
“…Over this range, the estimated accuracy (precision) for water vapor ranges from 4% to 19% (4%–15%, Livesey et al., 2020), based on both retrieval characterization and validation with independent measurements (Hurst et al., 2014; Lambert et al., 2007; Read et al., 2007; Vomel, Barnes, et al., 2007; Vömel, David, & Smith, 2007). The MLS data are broadly in agreement with correlative satellite data sets at this level, as addressed by the recent second SPARC data initiative and water vapor assessment (WAVAS‐II) activities (Hegglin et al., 2013; Khosrawi et al., 2018; Lossow et al., 2019). MLS data are screened according to the recommendations in the Aura MLS version 4.2 data quality document (Livesey et al., 2020).…”
Section: Correlative Data and Methodssupporting
confidence: 74%
See 2 more Smart Citations
“…Over this range, the estimated accuracy (precision) for water vapor ranges from 4% to 19% (4%–15%, Livesey et al., 2020), based on both retrieval characterization and validation with independent measurements (Hurst et al., 2014; Lambert et al., 2007; Read et al., 2007; Vomel, Barnes, et al., 2007; Vömel, David, & Smith, 2007). The MLS data are broadly in agreement with correlative satellite data sets at this level, as addressed by the recent second SPARC data initiative and water vapor assessment (WAVAS‐II) activities (Hegglin et al., 2013; Khosrawi et al., 2018; Lossow et al., 2019). MLS data are screened according to the recommendations in the Aura MLS version 4.2 data quality document (Livesey et al., 2020).…”
Section: Correlative Data and Methodssupporting
confidence: 74%
“…Validation efforts for ACE‐FTS v3.5 data have demonstrated that the water vapor product has good stability and mean bias within 10% (17–70 km) in comparison to the Michelson Interferometer for Passive Atmospheric Sounding (MIPAS) and Aura MLS measurements (Sheese et al., 2017). The assessment of ACE‐FTS data in WAVAS‐II also corroborates these results (Khosrawi et al., 2018; Lossow et al., 2019).…”
Section: Correlative Data and Methodssupporting
confidence: 70%
See 1 more Smart Citation
“…(2002) also reported some cases when the dehydrated air was observed downwind from mountain wave‐induced polar stratospheric clouds (PSCs). Since ILAS, different satellite sensors allowed a continuous monitoring of the stratospheric water vapor distribution (Khosrawi et al., 2018; Lossow et al., 2019). Especially, the remote‐sensing observations by the Microwave Limb Sounder (MLS) onboard of the Upper Atmosphere Research Satellite (UARS) and the Earth Observing System (EOS) on Aura (e.g., Herman et al., 2002; Nedoluha et al., 2002) have been used to document Arctic dehydration.…”
Section: Introductionmentioning
confidence: 99%
“…The MIPAS ozone product was thoroughly investigated within the European Space Agency's Climate Change Initiative (Laeng et al, 2014). The MIPAS water vapour product has been validated within the framework of the Stratosphere-troposphere Processes And their Role in Climate (SPARC) Water Vapor Assessment activity (Lossow et al, 2017(Lossow et al, , 2018. A high bias in the lower part of MIPAS N 2 O retrievals is discussed and partly remedied by Plieninger et al (2015).…”
Section: Mipasmentioning
confidence: 99%